Personalized approach to childhood obesity: Lessons from gut microbiota and omics studies. Narrative review and insights from the 29th European childhood obesity congress - BEREKET, ABDULLAH (WILEY, 2021)
The traditional approach to childhood obesity prevention and treatment should fit most patients, but misdiagnosis and treatment failure could be observed in some cases that lie away from average as part of individual variation or misclassification. Here, we reflect on the contributions that high-throughput technologies such as next-generation sequencing, mass spectrometry-based metabolomics and microbiome analysis make towards a personalized medicine approach to childhood obesity. We hypothesize that diagnosing a child as someone with obesity captures only part of the phenotype; and that metabolomics, genomics, transcriptomics and analyses of the gut microbiome, could add precision to the term obese, providing novel corresponding biomarkers. Identifying a cluster-omic signature in a given child can thus facilitate the development of personalized prognostic, diagnostic, and therapeutic approaches. It can also be applied to the monitoring of symptoms/signs evolution, treatment choices and efficacy, predisposition to drug-related side effects and potential relapse. This article is a narrative review of the literature and summary of the main observations, conclusions and perspectives raised during the annual meeting of the European Childhood Obesity Group. Authors discuss some recent advances and future perspectives on utilizing a systems approach to understanding and managing childhood obesity in the context of the existing omics data.
Keywords: genomics; metabolomics; microbiome; multi-omics; obesity; transcriptomics; BODY-MASS INDEX; EARLY-LIFE; INTESTINAL MICROBIOTA; WEIGHT-GAIN; FECAL MICROBIOTA; POOLED ANALYSIS; RISK-FACTORS; ASSOCIATION; OVERWEIGHT; CHILDREN